Relationships between test anxiety, self-regulation and strategies for coping with stress, in professional examination candidates - Amate Romera, Jorge; de la Fuente, Jesús (Anales de Psicología / Annals of Psychology, 2021)
The research objective was to establish relationships of association, interdependence and structural prediction between the variables of test anxiety, self-regulation and stress coping strategies. The theoretical framework of reference was the Studying, Learning and Performing under Stress (SLPS) Competency Model. Participating were 142 students who were preparing for professional examinations to attain a post as public school teacher (primary education), enrolled at academies in Almería (Spain) for this purpose. Previously validated questionnaires were administered for data collection. The study design was linear ex post-facto, with bivariate, inferential analyses of association (ANOVAs and MANOVAs) and of structural prediction. Results showed a negative relationship between test anxiety self-regulation, especially in students with high emotionality, and a negative impact on decision making. Positive relationships were found between test anxiety and strategies for coping with stress. Finally, a positive predictive relationship was verified between self-regulation and coping strategies, while associative and inferential analyses highlighted the role of goals as determining factors in strategies used for coping with stress, especially strategies that focus on problem solving. Results are discussed and implications for improving these processes in professional examination candidates are established.